Mechanical degradation and microcrack evolution of weathered basalt under freeze–thaw cycles - Chen, Jiayi; Wang, Lianjun; Wu, Guang; He, Liu; Bai, Liwei (Frontiers in Earth Science, 2026)
Freeze-thaw cycles (FTCs) play an important role in the degradation of rock masses and the stability of slopes in cold, high-altitude regions. However, the degradation behaviour of basalt with different weathering degrees under freeze-thaw (F-T) conditions remains insufficiently understood. In this study, basalt samples collected from a bridge foundation slope in an alpine mountainous region were subjected to 100 FTCs in laboratory. The degradation was investigated through measuring the P-wave velocity, porosity, uniaxial compressive strength, and direct shear strength. Microstructural damage in basalt was examined by scanning electron microscopy (SEM) at different freeze-thaw stages. The experimental results indicate that moderately weathered basalt exhibits more severe freeze-thaw-induced degradation than slightly weathered basalt. This difference is reflected in larger increases in porosity and greater reductions in P-wave velocity and mechanical strength. SEM observations show the microcracks propagation and structural degradation induced by FTCs. On the basis of the experimental results, an empirical model between strength degradation and easily measurable physical parameters was developed. The experimental evidence obtained in this work contributes to the understanding of freeze-thaw-induced degradation of basalt. It also offers practical support for engineering design and evaluation of rock slopes subjected to repeated freeze–thaw effects.